2020 New World Order. Issue 4 (28th September 2020) - Wallace, Beverly
Abstract: This paper proposes that as the nation move toward the 2020 election, civil harmony might be possible with an ideological shift. Using the words of writer Sylvia Wynter in her work, " 1492: New World View" who suggest that although this country was structured with domination and subjugation from its inception, this nation could be reimagined to embrace diverse people co‐existing. Understanding too that reconciliation must be defined by those who are marginalized, the author using an Afro‐futuristic ideology for a 2020 New World Order suggest that the Black Lives Matter movement could carry the torch.